The Challenges and Panaceas to Power Distribution Losses in Nigeria - Mohammed, O. O.; Otuoze, A. O.; Salisu, S.; Abioye, A. E.; Usman, A. M.; Alao, R. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Energy losses in the distribution network and its subsystems have been issues of great concerns in Nigeria’s power sector. For decades, several studies have been conducted on the challenges facing the power sector in Nigeria with most focus directed on the distribution subsystems. The major challenge in the distribution system is the high energy losses which are detrimental to the techno-economic benefits of the power systems. However, details of the distribution system challenges and the probable solutions have not been efficiently presented. In this study, some of these challenges are presented and the potential solutions are proposed. The features of the Nigeria distribution network, the technical and non-technical sources of losses as well as the identified challenges are presented before discussing the potential solutions. The panaceas so provided were from the understanding of some published works and other related materials as well as the in-depth understanding of the authors. This article can serve as a guide for the utilities and stakeholders in the power sector for efficient management operations and improved customer service delivery.